Analysis for effect of pores on acoustic performance of reactive muffler. (October 2021) - Hujare, Pravin P; Mote, Vishal R; Mache, Ashok R; Hujare, Deepak P; Kore, Sandeep S
The major source of noise pollution was an internal combustion engine. Henceforth, the design of the engine exhaust system was a tough challenge for automotive industries. The mufflers have been used to moderate the exhaust noise from the engine to the neighboring atmosphere. So in domestic as well as the industrial application, it is required to reduce noise levels to prevent human hazards. The performance of muffler is measured in terms of transmission loss. The transmission loss of reactive muffler is depending on its geometry. This article describes the effects of pores at the inlet pipe and outlet pipe of the reactive muffler on its performance capacity at a target frequency. It is found that the muffler performance is dependent on the number and position of pores. The single chamber and double chamber reactive mufflers are used for the study. The numerical analysis is performed by COMSOL Multiphysics software. The numerical analysis result of the different models of the muffler is compared with experimental analysis. The purpose of the study is to investigate the effect of pores in inlet and outlet pipe to maximize the TL at the target frequency of reactive muffler.